Splenic injury is an under-recognized adverse event of in-patient colonoscopy: a nationwide analysis - Cortés, Pedro; Corral, Juan E.; Umar, Shifa; Bilal, Mohammad; Brahmbhatt, Bhaumik; Farraye, Francis A.; Kroner, Paul T. (Endoscopy International Open, 2022)
Background and study aims Splenic injury (SI) during colonoscopy is an underappreciated adverse event. Our aim was to examine the occurrence and outcomes of patients who developed SI after inpatient colonoscopy using a nationwide dataset.Patients and methods Retrospective, observational study using the National Inpatient Sample (NIS) between 2012 and 2018. All patients with ICD9/10CM procedural codes for colonoscopy with or without SI were included. The primary outcome was the association between SI and inpatient colonoscopy. Secondary outcomes were inpatient morbidity, mortality, resource utilization, splenectomy rates, hospital length of stay and total hospital costs and charges. Comparative analyses were performed between patients with and without SI. Multivariate regression analyses were utilized.Results A total of 2,258,040 of inpatient colonoscopies were included. Of these, 240 had associated SI and 25 patients required splenectomy (10.4 %). The incidence of colonoscopy-associated SI remained relatively stable between 2012 and 2018 (0.033 % versus 0.020 %, respectively). The mean age of patients with and without SI was 63.7 and 64.1 years, respectively. The occurrence of SI was calculated as 10.63 cases per 100,000 inpatient colonoscopies. Patients who had associated SI displayed significantly higher odds of inpatient mortality (aOR: 14.45) and ICU stay (aOR: 10.11) compared to those without SI.Conclusions Splenic injury confers significantly higher odds of inpatient mortality, and resource utilization. The incidence of SI related to colonoscopy remained stable during the study period. Although uncommon, SI should be considered when encountering patients with abdominal pain after colonoscopy.